Analysis Regarding Quality of Life of Menopausal Women on Clinical Disorders during Menopausal Period, on Sukomanunggal Sub-District Surabaya in 2019 - Salmon Charles Siahaan; Hendera Henderi; Ardelia C V; Ridzal W; Azyvati KP (Fakultas Kedokteran Universitas Lambung Mangkurat, 2019)
Abstract: Approximately 70% of women in the peri period and post menopause experience vasomotor complaints, depression, psychological and somatic complaints. The severity of the symptoms will be different for each woman. This research was conducted to find out whether the clinical symptoms that appear in menopausal women will cause disruption to quality of life. This study was conducted on menopausal women at Geriatric Poly at Simomulyo Health Center Surabaya in March - April 2019 using cross sectional method. Questionnaire was used to measure clinical symptoms in menopausal women and the QOLWHO-BREF questionnaire to assess the quality of life of menopausal women. Menopausal women in this study were at the age of 60.89 + 6.55 years. Menarche at the age of 12.49 + 1.74 years and Menopause at 49.41 + 4.88 years. For the BMI category mean at 24.33 + 4.02 kg / m2. Based on contraception used, it was found that most of women used combination pills (36.8%). Menopausal complaints consist of physical complaints and psychological complaints, for the major complaints from physical are complaints regarding bone and joint pain (86.5%) and for major complaints from psychological factor is a decrease in sexual desire (72.9%). The category of the amount of variety clinical symptoms that appear in each woman, it was found that at most of menopausal women felt 3 complaints (67.6%; 13.24 + 1.76). For the quality of life (WHOQOL) results, the overall quality of life criteria is in the very bad and bad category with the environmental domain being the lowest (3.04 + 10.93) and the better category compare than the other is the social relations domain (29.82 + 4.74) . The results of data analysis through the Spearman correlation test showed that there was a relationship between the number of complaints with a decrease in quality of life (Z = 3.15433; p = 0.00164) and it was found that menopausal women with complaints of menopause affected the decrease quality of life (Z = -4.30769; p <0.00001). Based on this study it was found that the factors that significantly influence the quality of life of a menopausal woman are clinical symptoms that appear both from physical symptoms and psychological symptoms. appears also has a significant effect on decreasing the quality of life of a menopausal woman Keyword: Menopause, clinical symtoms, quality of life